THE RELATIONSHIP BETWEEN AUTONOMY, WORKLOAD, AND WORK-LIFE BALANCE TO JOB PERFORMANCE OF FEMALE LECTURERS AT PRIVATE UNIVERSITIES DURING PANDEMIC COVID -19 - Meilani, Yohana F. Cahya Palupi; Bernarto, Innocentius; Nahar, Faiza Husnayeni (Universitas Brawijaya, Indonesia, 2022)
The urgency of this research is to see the performance of female lecturers during the COVID-19 pandemic. This study aimed to analyze the relationship of each variable, namely autonomy, workload and work-life balance, to the job performance of female lecturers at private universities during pandemic covid-19. This type of research is quantitative research. The object of this research is female lecturers at private universities in Tangerang, Indonesia. The sampling used purposive sampling techniques. The analytical tool used is the multiple regression used program SPSS. The results show a positive relationship between autonomy and job performance. Then, the workload has a negative relationship with job performance. Also, work-life balance has a positive relationship with job performance. The managerial implication found in this study shows that this research can give input to private university managers to manage female lecturer performance during pandemic Covid-19. Future researchers areÂ expected to research lecturers at private and nonprivate Universities. The contribution of this research expected can give input to private university managers to manage female lecturer performance during pandemic Covid-19.